The Problems of Application Online Learning in the Affective and Psychomotor Domains during the Pandemic - Susanto Susanto; Yahmun Yahmun (ANFA MEDIATAMA, 2022)
The outbreak of the Covid-19 virus has had an impact not only on the decline of the people's economy but also on the education system in Indonesia. As a result, the learning process is shifted to online learning. The application of online learning is inseparable from various problems, not only concerning facilities and infrastructure but also regarding the goals of education itself. The purpose of this study was to determine the problems of the application of online learning, especially in the affective and psychomotor domains. This research is a qualitative descriptive study. Sources of data obtained through interviews with research subjects in STKIP PGRI Trenggalek. The results obtained indicate that the problems in the application of online learning in the affective and psychomotor domains concern student learning interests, the value of honesty and a sense of student responsibility, and student discipline. Meanwhile, in the psychomotor realm, the problem found is related to the implementation of English lecturer practice or assessment of student skills.